Interaural time delay personalisation using incomplete head scans - Gamper, Hannes; Johnston, David; Tashev, Ivan (Proc. ICASSP, 2017)
When using a set of generic head-related transfer functions (HRTFs) for spatial sound rendering, personalisation can be considered to minimise localisation errors. This typically involves tuning the characteristics of the HRTFs or a parametric model according to the listener’s anthropometry. However, measuring anthropometric features directly remains a challenge in practical applications, and the mapping between anthropometric and acoustic features is an open research problem. Here we propose matching a face template to a listener’s head scan or depth image to extract anthropometric information. The deformation of the template is used to personalise the interaural time differences (ITDs) of a generic HRTF set. The proposed method is shown to outperform reference methods when used with high-resolution 3-D scans. Experiments with single-frame depth images indicate that the method is applicable to lower resolution or partial scans which are quicker and easier to obtain than full 3-D scans. These results suggest that the proposed method may be a viable option for ITD personalisation in practical applications.